Maximum energy efficiency tracking for wireless power transfer systems - Zhong,WX; Hui,SYR (IEEE Transactions on Power Electronics, 2015)
A method for automatic “maximum energy efficiency tracking” operation for wireless power transfer (WPT) systems is presented in this paper. Using the switched-mode converter in the receiver module to emulate the optimal load value, the proposed method follows the maximum energy efficiency operating points of a WPT system by searching for the minimum input power operating point for a given output power. Because the searching process is carried out on the transmitter side, the proposal does not require any wireless communication feedback from the receiver side. The control scheme has been successfully demonstrated in a two-coil system under both weak and strong magnetic coupling conditions. Experimental results are included to confirm its feasibility.